PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT MELALUI ZAKAT - Tsabit, Ahmad Majdi (IAIN Ambon, 2019)
The writing ofthis article aims to determine the relevance of zakat with welfare instruments. Where inthe process of achieving welfare, an instrument in the form of zakat is needed. Zakat is an independent social aid which is a duty for rich people to help those who are poor so that they can get out of poverty. With zakat, poverty levels are expected to be reduced. Welfare in the perspective of Islamic economics is the fulfillment of material and non-material needs, the world and the end based on personal and community awareness to obey and obey (aware) of the law desired by Allah through His instructions in the Qur'an, through examples in the example of the Prophet Muhammad Saw, and through ijtihad and the good of the scholars. Therefore, welfare is not an ideal without sacrifice, but requires continuous and continuous struggle. Keywords: Prosperity, Society, Economy, Zakat